Water Quality Monitoring of Tigris River by Using (GIS)-Based Physicochemical â€ŽParameters in Baghdad, Iraq - Nazhat Sabeeh, Nadia; M. Sh. Alabdraba, Waleed; Hasan Mohamed, Ghadah; B. Mohammed, Zainab (International Journal of Engineering and Technology, 2018)
Water quality deterioration has become an essential concern worldwide due to climatic â€Žchanges and increased pollution. As a result, the available drinking water supply resourcesâ€ â€will receive its ration of this deterioration. This study was conducted to monitor the water â€Žquality of the Tigris River in eight different locations in Baghdad during the period â€Žbetween 2005 and 2013. Water samples were collected and analyzed for fourteen â€Žselected physicochemical parameters including alkalinity, total hardness (TH), turbidity, â€Žtotal suspended solids (TSS), temperature, pH, nitrate, nitrite, phosphate, electrical â€Žconductivity (EC), chloride, calcium, magnesium, and sulfate. To show the spatial and â€Žtemporal variations of the selected parameters along the study area easily and objectively, â€ŽGeographical Information System maps (GIS maps) were used. Results showed that the â€Žobtained values in winter of alkalinity, turbidity, electrical conductivity, and the â€Žconcentration of calcium, magnesium, sulfate, nitrite, phosphate, chloride, and total â€Žsuspended solids were higher as compared with the corresponding values in summer. On â€Žthe other hand, temperature, total hardness, pH, and nitrate values were higher in summer â€Žas compared with the corresponding values in winter. The water quality of Tigris River â€Žthroughout the study period was within the permissible limits of the Iraqi standards for â€Ždrinking water.â€ŽÂ